Opioid Crisis Effects on Municipal Finance. (22nd June 2021) - Cornaggia, Kimberly; Hund, John; Nguyen, Giang; Ye, Zihan
Abstract: We investigate the effects of opioid abuse on municipal finance. We employ instrumental variables, border discontinuity difference-in-differences regressions, and coarsened exact matching to identify consistent causal effects, while controlling for variation in economic conditions and demographics. Opioid abuse lowers credit ratings, increases new offer yields, and reduces bond issuance. Reversal of these effects following effective antiopioid legislation further supports causality. Differential effects due to investor heterogeneity suggest that opioid abuse affects municipal finance through a capital supply channel. Overall, we conclude that local opioid abuse impedes municipalities' access to capital and thus hurts their ability to provide public services and infrastructure.